ALGORITMA OPTIMISASI WHALE UNTUK DIAGNOSTIK MEDIS: REVIEW LITERATUR SECARA SISTEMATIS - Septian, Firza; Utami, Ema (SISKOMTI: Jurnal Sistem Informasi Komputer dan Teknologi Informasi, 2022)
A lot of factors, including noise, have a harmful impact on the health of people from all walks of life, including unborn children. In the medical field, grouping research utilizing WOA was required. Data is gathered from a number of reliable sources, including IEEE and Scopus. Practical applications serve as a "Laboratory" in the action research methodology for testing theories. on items that have been synthesized. Regarding WOA for medicinal purposes, there are three basic concepts. The plan calls for the use of WOA for medical diagnostic. A population-based method called the Whale Optimization Method (WOA) uses a randomized collectivist humpback whale sample to improve prospective solutions. Three of the 74 journals gathered satisfied the predetermined criteria.